Mansoura city general planning in Sindh (Journal of the College of Basic Education, 2022)
The general planning of the city of Mansoura in the country of Sindh is considered one of the important studies because most of the studies and researches were particularly concerned with the planning of Arab cities.Where the Muslim Arabs had a prominent role in the Arab Islamic conquests, not only on the military level, but also on the civilized level, as they were credited with establishing many cities.As the naming of the city of Mansoura goes back to the victories achieved by Muhammad bin Al-Qasim Al-Thaqafi over the ruler of Sindh, and that its foundation was near an ancient place called - Barhamnabadh - and not what I think that it was built in the same place as -Barhamnabadh -.The Arab influence was prominent on the engineering and urban planning of the city of Mansoura due to the settlement of the Arab tribes in it, as well as the mastery of its inhabitants of the Arabic language in addition to their mother tongue, Sindhi, and their adoption of the style.